Significance Impact of Seafood Processing Wastewater Effluent - Zulkipli, Muhammad Asyraf; Abu Bakar, Juliza; Radin Mohamed, Radin Maya Saphira; Saeed Al-Gheethi, Adel Ali (Penerbit UTHM, 2020)
Seafood is one of the high food demands in Malaysia as it obtained 15% of the protein which required food dietary hierarchy. According to the Fisheries Department of Malaysia (DOF), approximately 5% of fisheries production is increased each year since 2013. Therefore, this chapter provides insights into a range of aspects associated with the statistics of seafood production, method of seafood processing, impact of improper discharge, criteria, chemical characteristics of the seafood processing wastewater, standard regulation of seafood processing discharge and previous studies on seafood processing wastewater treatment. Therefore, it improved the awareness towards the untreated of seafood processing wastewater.